Assessment of groundwater quality in Randublatung Groundwater Basin. Issue 1 (1st March 2022) - Hartono, A; Hendrayana, H; Akmaluddin,
Abstract: Groundwater is used for domestic and industrial water supply and irrigation. Land use in the Randublatung groundwater basin is mainly agricultural, using groundwater as the primary source. The present study aims to assess the groundwater quality in Randublatung groundwater basin. Groundwater quality in the study area, 13 groundwater samples were collected and analyzed for various parameters. Physicochemical parameters of groundwater such as Electrical conductivity (EC), total dissolved solids (TDS), pH, Chloride (Cl), Calcium (Ca), Magnesium (Mg), Sodium (Na), Potassium (K), Sulfate (SO4), Bicarbonate (HCO3), Nitrate (NO3) were determined. A chemical index like percentage of sodium, sodium adsorption ratio (SAR), permeability index (PI), Kelly Index, and Magnesium ratio can be used to determine groundwater quality for irrigation. From the study, 3 of 13 samples are suitable for drinking. Based on Wilcox classification, 23% of the groundwater samples are suitable for irrigation. From the USSL chart, there are four types of water quality. All groundwater samples are in a low sodium hazard condition based on the sodium absorption ratio. The permeability index and magnesium ratio indicate that all groundwater samples are of good quality for irrigation utility. Based on the Kelly index, there is one sample unsuitable for irrigation.